Adobe Flash CS6 revealed - Shuman, James E. (Delmar, Cencage Learning, 2013)
Introduces students to Adobe[Registered] Flash[Registered] CS6 Professional, the industry-standard software for developing interactive experiences on the Web, desktops, mobile devices, and tablets. This book includes in-text icons, end-of-chapter projects, helpful data files, and a robust suite of supplemental learning and teaching tools